Affliction in the post Palu disaster: State failure to implement human rights standard on disaster management - Aktieva Tri Tjitrawati; Mochamad Kevin Romadhona (Cogent Social Sciences)
The purpose of this paper is to evaluate how the State implement human rights standard on disaster management and response in Indonesia to explore the State’s obligation to provide fundamental rights in a state of exigency. This paper investigates whether the law and regulation on disaster management in Indonesia have adopted human rights standards and how the standard has been implemented after Palu Disaster that occurred on 28 September 2018. The investigation was conducted through field research using a standard human rights implementation criteria-based questionnaire according to the standard set by The Core Humanitarian Standard on Quality and Accountability (CHS) 2014. The research was preceded by an FGD held by stakeholders to obtain more elaborate and balanced information between the disaster victims and the government. Reports of discriminative treatment received by the victims and poor basic needs distribution during the disaster are a few clues regarding the lack of implementation of human rights standards in disaster management in Palu. Here a twist happened between the weakness of human rights protection under the regulation of disaster management and the tendency of state authority to use a positive-legalistic approach to implement such regulation.